Cultural due diligence in hospitality ventures : a methodological approach for joint ventures of local communities and companies - Häusler, Nicole, 1964- (Tourism, hospitality & event management., 2017)
This book introduces readers to a powerful method for cross-cultural due diligence in mergers and organizational collaborations. It employs the context of joint ventures between local communities and companies in the domain of hospitality in emerging tourism destinations. The book first analyzes the impact of cultural diversity in mergers between local communities and the private sector, revealing the characteristics and functions of culture and paying specific attention to the roles of organizational and community cultures in hospitality. In two subsequent methodological chapters the book presents a theoretical framework for cultural due diligence and identifies the principal actors, technical aspects and core principles. On the basis of a separate case study from northern Thailand, the book provides an example of cultural context analysis and presents the findings and results. In a concluding chapter the book presents an outlook on further research and development in this field.